El Proyecto Gutenberg (1971-2009) - Lebert, Marie (Salt Lake City, UT : Project Gutenberg, 2010)
"El Proyecto Gutenberg (1971-2009)" by Marie Lebert is a historical account detailing the origins and development of the influential Project Gutenberg, which aims to digitize literary works and disseminate them freely over the internet. Written in the early 21st century, the book explores a significant technological advancement$1 (Bthe creation of the first digital library, which originated with Michael Hart's vision in 1971. It likely focuses on topics related to digital literature, public domain rights, and the evolution of eBooks. The narrative chronicles the inception of Project Gutenberg, starting with Hart's groundbreaking digitization of "The United States Declaration of Independence." It illustrates the project's evolution over nearly four decades, detailing milestones such as the transition from ASCII text to a more comprehensive array of digital formats, the rapid growth of available titles, and the decentralized collaboration of volunteers for proofreading and digitalization. The book also addresses challenges, such as copyright issues affecting public domain works, and highlights the project's vision to make literature accessible to everyone, thereby democratizing knowledge and fostering a culture of free information sharing. (This is an automatically generated summary.)s
Release date is 2010-03-13
Produced by Al Haines
Keywords: Project Gutenberg